Reliable HPLC Determination of Aflatoxin M1 in Eggs - Mostafa M. H. Khalil; Ahmed M. Gomaa; Ahmed Salem Sebaei (Journal of Analytical Methods in Chemistry)
Aflatoxin M1 is the foremost metabolite of aflatoxin B1 in humans and animals, which may be present in animal products from animals fed with aflatoxin B1 contaminated feed. In this study a high performance liquid chromatography method for determination of aflatoxin M1 in eggs was described. The egg samples were diluted with warmed water and the toxin was immunoextracted followed by fluorescence detection. The average recovery of aflatoxin M1 at the three different levels 0.05, 0.1, and 0.5 μg/kg varied between 87% and 98%. The method is linear from the limit of quantification 0.05 μg/kg up to 3 μg/kg levels. This method is intended for aflatoxin M1 analyses in eggs simply with minimum toxin lose, excellent recovery, and accurate results with the limit of detection 0.01 μg/kg.